"Africa is our Fatherland": The Black Atlantic, Globalization, and Modern African Christianity. Issue 2 (July 2014) - Hanciles, Jehu J.
This essay makes the case that in the nineteenth century extensive migration and interactions among Africans in the black Atlantic world provided strong impetus for the growth of African Christianity. The relocation of huge segments of the African population (to regions of Western Europe and the Americas bordering the Atlantic) represented a major strand of globalization processes. This development was no less significant than the intercontinental economic system that produced unprecedented African dispersion in the first place. European aid and agency certainly played a crucial role in unfolding developments, reaching a crescendo in the late nineteenth century. But the transfer of people and ideas from the African diaspora, as well as the initiatives triggered by indigenous African responses, produced alternative and sometimes countervailing movements of extraordinary impact. These proved decisive for the spread of Christianity in Africa and beyond. As a symbol of massive migrations and transnational connections, the black Atlantic exemplifies the global–local interactions and the multidirectional processes that mark the worldwide expansion of the Christian faith.